2018
DOI: 10.1186/s12885-018-4870-z
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic potential of N-terminal deletion and S45Y mutant β-catenin in promoting hepatocellular carcinoma development in mice

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide with limited treatment options. Mutation of β-catenin is one of the most frequent genetic events along hepatocarcinogenesis. β-catenin mutations can be in the form of point mutation or large N-terminal deletion. Studies suggested that different β-catenin mutations might have distinct oncogenic potential.MethodsWe tested the oncogenic activity of β-cateninS45Y, one of the most frequent point mutations of β-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
(35 reference statements)
3
21
0
Order By: Relevance
“…These findings are in keeping with the focal nuclear/cytoplasmic β-catenin localization that we observed in both of our β-catenin-driven HCC models (Fig. 5B–F) (Evason et al, 2015) and that is characteristic of human HCC (Evason et al, 2015; Friemel et al, 2015; Qiao et al, 2018; Rebouissou et al, 2016). Our results support the hypothesis that heterogeneity in β-catenin immunostaining is due to heterogeneous β-catenin activity and not due to limitations in detection of β-catenin protein.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in keeping with the focal nuclear/cytoplasmic β-catenin localization that we observed in both of our β-catenin-driven HCC models (Fig. 5B–F) (Evason et al, 2015) and that is characteristic of human HCC (Evason et al, 2015; Friemel et al, 2015; Qiao et al, 2018; Rebouissou et al, 2016). Our results support the hypothesis that heterogeneity in β-catenin immunostaining is due to heterogeneous β-catenin activity and not due to limitations in detection of β-catenin protein.…”
Section: Discussionsupporting
confidence: 92%
“…Eighty-seven percent of HCC show intratumor heterogeneity with respect to morphology, immunohistochemistry and/or mutational status of CTNNB1 or TP53 (Friemel et al, 2015). In β-catenin-driven HCC, CTNNB1 mutations are generally ubiquitous within each tumor (Torrecilla et al, 2017), but nuclear and cytoplasmic localization of β-catenin is heterogeneous in both animal models (Evason et al, 2015; Qiao et al, 2018) and patients (Friemel et al, 2015; Rebouissou et al, 2016). For example, we previously reported that hepatocyte-specific expression of activated β-catenin in zebrafish [ Tg(fabp10a : pt-β-cat) ] leads to HCC in 78% of animals by 6 months post fertilization (mpf) (Evason et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…That ⌬(90) generates HBs or HCCs based on whether it is co-expressed with YAP S127A or c-Met lends further credence to the argument that ␤-catenindriven tumorigenesis can be promiscuous and influenced by other co-expressed oncoproteins as well as age-and tissue-specific factors (70). We did not examine the S45Y mutant used by Qiao et al (70) but think it likely that it would also drive HB tumorigenesis in association with YAP S127A , given the robust tumorigenicity of S45A, S45F, and S45P (Fig. 1B).…”
Section: ␤-Catenin Mutations and Hepatoblastoma Phenotypesmentioning
confidence: 99%
“…Hydrodynamic tail vein injection was performed basically as previously described. [17][18][19] Briefly, 20 mg of either pT3-EF1ab-catenin-WT, K335I, or N387K construct was mixed with 20 mg pT3-EF1a-c-Met and 1.6 mg pCMV/SB in 2 mL saline. This solution was injected in the lateral tail vein of 6-to 8-week-old WT FVB/N mice purchased from The Jackson Laboratory (Sacramento, CA).…”
Section: Mice and Hydrodynamic Tail Injectionmentioning
confidence: 99%